Characterisation of wheat germ plasm against Helminthosporium leaf blight - and R.B. SINGH, M. RAGIBA, K.V. PRABHU (Indian Phytopathology, 2002)
567 wheat entries were screened against the natural infection of Helminthosporium leaf blight disease in the hot spot region, Pusa, Bihar to identify the resistant lines. Out of 567 entries screened, 57 were resistant (R), 123 moderately resistant (MR), 291 moderately susceptible (MS), 88 susceptible (S) and 8 highly susceptible. Among the resistant lines, Chirya - 3 and Mayoor from CIMMYT, Mexico showed high degree of resistance to the disease under field conditions. Based on the disease reaction, twenty promising resistant genotypes characterized for different levels of resistance and seven highly susceptible cultivars were isolated for further testing under artificial epiphytotic conditions for genetic analysis and their potential in breeding for HLB resistance.